2023
DOI: 10.2478/enr-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between preoperative calcium and parathormone levels with parathyroid gland volume

Abstract: Objective. Hyperparathyroidism is a prevalent disease with parathyroid adenomas being the most common cause. Surgical excision remains the standard treatment for parathyroid adenoma. Successful preoperative localization of the parathyroid adenoma could facilitate the decision regarding the extent of surgical exploration. The aim of the current study was to assess the correlation between the preoperative values of parathyroid hormone and ionized calcium with the adenoma weight and volume in patient with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
1
1
Order By: Relevance
“…Previous studies have reported correlations between parathyroid size or weight and peripheral calcium or PTH levels. 17 , 21 , 39 However, compared with previous reports, we found the highest correlation coefficients. We collected calcium and PTH levels before any medical or nonmedical (i.e., hyperhydration) intervention.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have reported correlations between parathyroid size or weight and peripheral calcium or PTH levels. 17 , 21 , 39 However, compared with previous reports, we found the highest correlation coefficients. We collected calcium and PTH levels before any medical or nonmedical (i.e., hyperhydration) intervention.…”
Section: Discussioncontrasting
confidence: 73%
“…In a study, it was found that the risk of postoperative hypocalcemia increases as the thyroid gland volume decreases (23). In another study, it was reported that the risk of hypocalcemia increased in those with a small thyroid volume and the risk of bleeding in those with a large thyroid volume (24). In our study, it was determined that the increase in thyroid volume had a statistically significant effect on hypocalcemia, albeit at a low level.…”
Section: Discussionsupporting
confidence: 43%
“…There are many methods to evaluate the correlation, such as Pearson correlation and Spearman correlation. The degree of connection between preoperative calcium and parathyroid hormone levels and parathyroid volume was assessed using the correlation coefficient by Emad R et al [7] . The research results will help the surgeon to predict operation to avoid unnecessary.…”
Section: Correlation Analysismentioning
confidence: 99%